ASSESSMENT OF GENETIC DIVERGENCE AMONG SUGARCANE GENOTYPES (Saccharum officinarum L.) BASED ON MOLECULAR MARKERS - NAVEEN ARORA; LENIKA KASHYAP; R S GILL (The Bioscan, 2024)
The success of any crop improvement program depends upon the available genetic diversity as well as the kind and magnitude of variation. In the present studies a set of fifty-two visually chosen agronomically superior genotypes were analyzed for genetic diversity at molecular level. From a total of forty-one simple sequence repeats markers, thirty - two polymorphic markers revealed eighty-four alleles/bands indicating 2.64 alleles per locus. Polymorphism information content (PIC) value ranged from 0.17 to 0.74 with a mean value of 0.54 indicating a moderate level of genetic diversity in the test material. On the basis of DARwin’s Dice dissimilarity coefficient fifty-two genotypes were grouped into seven distinct clusters. The estimated values of genetic dissimilarity ranged from 0.224 to 0.535. The cluster I was the largest with 15 genotypes while cluster VI and VII had only one genotype each. The parentage of genotypes did not have any effect on clustering pattern and the genotypes of bi parental crosses were found to be distributed more widely. Genotypes CoJ 85 and S877/07 were the most divergent. The material under our study has indicated a good level of variability and genetic diversity. The potential of SSR markers in diversity analysis is also demonstrated.